Components of Labor Productivity Growth in the Food System, 1958-67 - Schluter, Gerald; Beeson, Patty (The Review of Economics and Statistics, 1981)
T WO economic problems which would be on many people's list of crucial and interesting contemporary economic issues would be food costs and a recent slowing in the growth of labor productivity. These issues are interrelated. For years we had the phenomenon of a growing demand for food exceeded by an even faster growing supply of food. In recent years, there have been some changes. Labor productivity is still growing faster in the farm sector than in the nonfarm sector but the share of personal income spent for food has stabilized in the 16%-17% range. Food prices have risen and have been an important contributor to inflation. At the same time the farmers' share of the food dollar has dropped and the amount of embodied services in food purchased by consumers has risen. The well-being of an economy can be enhanced by the growth in available resources, or a more effective use of these resources. Thus, one way of lowering consumer food cost is increasing labor productivity. Obviously there are a variety of forces in operation in this situation and any attempt at partial analysis may be found wanting. Confronted with this problem, Howe, Schluter and Handy (1976) chose to use an input/output model to study changes in labor productivity in the food system. In this paper we will review the Howe, Schluter and Handy (HSH) technique and results. We will then introduce a factoring technique that allows us to solve for the contribution to total productivity of each variable in the HSH technique. Finally, we will present and discuss our results.